Android-Based Stock Opname Application Development with SQLite and Firebase - Maulana, Ishaq; Yasin, Verdi; Yulianto, Akmal Budi (Jurnal Teknologi Informatika dan Komputer, 2025)
Stocktaking, or stock data matching, is a crucial activity in inventory management within a company. Through this process, the stock data recorded in the system is compared with the physical conditions in the field (Jims, 2023). This activity not only aims to ensure data accuracy (Tarigan, 2021) but also serves as an integral part of internal control within the company's supply chain. PT Multilindo Surya Cemerlang is a company engaged in the distribution and sales of electronic goods. Stocktaking is a crucial component in maintaining the accuracy of a company's inventory data. However, at PT Multilindo Surya Cemerlang, this process is still performed manually by recording on paper and then re-entering it into a computer. This method is quite time-consuming and carries the risk of recording errors. Therefore, this study aims to develop an Android-based application that can assist the stocktaking process directly in the field. The application is designed with SQLite database support for local storage and Firebase for online data storage and synchronization. The development was conducted using the SDLC (System Development Life Cycle) model with a waterfall approach, encompassing the stages of requirements analysis, system design, implementation, testing, and maintenance. Trial results demonstrated that the application was able to assist staff in recording stock more quickly and accurately, as well as simplifying the overall inventory data recapitulation process.